Analisis Penempatan Pegawai Mutasi dari Pemerintah Kabupaten/Kota ke Pemerintah Provinsi Sulawesi Tengah - Tawil, Novalinda; Hattab, Syahruddin; Ahsan, Sitti Cheariah (CV. Rayyan Dwi Bharata, 2025)
This study aims to determine the policy implementation of Civil Servant Transfers in the Regional Government of Central Sulawesi Province. In this research, the author uses Mifta Thoha's theory (2005:57), which consists of the following criteria: Length of service in a particular field, Organizational needs, Organizational refreshment, Knowledge, Skills, and Special reasons (following spouse). The research method used is descriptive qualitative. Data collection was carried out using observation, documentation, and interviews. The selection and number of informants in this study used purposive sampling technique, namely, parties who are considered to have in-depth knowledge regarding the research problem, totaling 5 (five) people. The data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions/verification. Based on the results of this study, it can be concluded that there are several issues that require special attention, namely related to the decline in employee motivation due to difficulties in adapting after the transfer, the policy of filling positions not based on existing skills, and regulations regarding the period of service for civil servant candidates of the 2019 cohort and onwards, which prohibit submitting transfer requests for any reason.